2016
DOI: 10.1007/s10549-016-3945-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multicomponent physical activity behavior change intervention on breast cancer survivor health status outcomes in a randomized controlled trial

Abstract: Purpose Little is known about the effects of physical activity behavior change interventions on health outcomes such as lower extremity dysfunction and SF-36 physical health (predictor of mortality) in breast cancer survivors. Furthermore, effect moderators are rarely reported. Therefore, we report the effects of the 3-month BEAT Cancer physical activity behavior change intervention on global health status and health indicators along with moderators of intervention outcomes. Methods Post-primary treatment br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…In our study, effects of the early rehabilitation program three months after surgery point to an increase in average summation scores in all domains and components in both patient groups. These results are also supported by studies done in Denmark, Poland, and Spain [2,17,19,20,25].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In our study, effects of the early rehabilitation program three months after surgery point to an increase in average summation scores in all domains and components in both patient groups. These results are also supported by studies done in Denmark, Poland, and Spain [2,17,19,20,25].…”
Section: Discussionsupporting
confidence: 74%
“…A heterogeneous rehabilitation approach with specific rehabilitation interventions and different methodological approaches are described in numerous studies [5-10, 12, 13]. Most authors reported their positive influence on the QoL of those suffering from and being treated for breast cancer [15][16][17][18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The first is the use of a commercially available product (NutriSystem®) during the first 24 weeks of the lifestyle modification for weight-loss. Earlier trials primarily used diet and/or physical activity and/or behavioral modification to achieve weight-loss [79]. …”
Section: Resultsmentioning
confidence: 99%
“…This survey is a widely used health survey which has been used extensively in breast cancer survivors [7379]. It includes 36 items covering eight health domains: physical functioning, bodily pain, role limitations due to physical health problems, role limitations due to personal or emotional problems, emotional well-being, social functioning, energy/fatigue, and general health perceptions.…”
Section: Methodsmentioning
confidence: 99%
“…A randomized controlled trial (RCT) revealed that BEAT Cancer improved quality of life, lower extremity function, and satisfaction with life in breast cancer survivors. Improvement in fatigue based on the SF-36 vitality scale was also noted [15]. The intervention benefit was larger in those with lower baseline scores and less support at home [16].…”
Section: Physical Activitymentioning
confidence: 99%